The relationship between Islamic index (Syariah index) and conventional index (finance index) in Bursa Malaysia, Kuala Lumpur / Dalila Daud, Omar Samad and Ahmad Marzuki Aminuddin - Daud, Dalila; Samad, Omar; Aminuddin, Ahmad Marzuki (2006)
The objectives of this study is to identify whether there is a significant relationship of Islamic and Conventional Indices between two sectors in Bursa Malaysia i.e., Syariah Index and Finance Index. The study covers six years including the period of millennium era from 17th April 1999 to 17th April 2005. Specifically, this study attempts to find out whether there is any correlation between Syariah Index and Finance Index. The test was conducted using the correlation to find the relationship between the indices and Causal & Granger to find the direction of causation. The basic concept used in this study is by analyzing quantitative data with the objective of finding relationship of these indices.